2014
DOI: 10.1038/ncomms4983
|View full text |Cite
|
Sign up to set email alerts
|

Amerindian-specific regions under positive selection harbour new lipid variants in Latinos

Abstract: Dyslipidemia and obesity are especially prevalent in populations with Amerindian backgrounds, such as Mexican–Americans, which predispose these populations to cardiovascular disease. Here we design an approach, known as the cross-population allele screen (CPAS), which we conduct prior to a genome-wide association study (GWAS) in 19,273 Europeans and Mexicans, in order to identify Amerindian risk genes in Mexicans. Utilizing CPAS to restrict the GWAS input variants to only those differing in frequency between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 74 publications
7
77
1
Order By: Relevance
“…Within the 11q23.3 region, we focused on chromosome 11:116,600,001-117,100,000 where previous GWAS fi ndings were localized ( 16,17,23,24 ). In order to identify the independent effects of candidate loci on TG, we used the following methods.…”
Section: Dissecting the 11q233 Regionmentioning
confidence: 99%
“…Within the 11q23.3 region, we focused on chromosome 11:116,600,001-117,100,000 where previous GWAS fi ndings were localized ( 16,17,23,24 ). In order to identify the independent effects of candidate loci on TG, we used the following methods.…”
Section: Dissecting the 11q233 Regionmentioning
confidence: 99%
“…We, thus, analyzed 11 SNPs, including 6 established TG-associated SNPs (collectively called “GWAS SNPs”, including rs964184, rs3135506, rs651821, rs662799, rs12225230, and rs139961185). 1019 As shown in Table 1, there was no tag SNP for rs147210663 nor rs11357208. The SNP rs2072560 had 3 tag SNPs (one of them, rs651821, was also identified in several published GWAS reports).…”
Section: Resultsmentioning
confidence: 99%
“…10, 1215, 19, 25, 37, 38 Previous studies in Amerindian-derived populations have identified strong associations between TG and variants in this chromosomal region, particularly rs964184. 14, 19, 39 SIK3 has been suggested as a functional candidate based on evidence for recent natural selection centered on rs139961185. 19 In our study, however, rs139961185 was not associated with TG after conditioning on rs964184 (Table S3 in the Data Supplement).…”
Section: Discussionmentioning
confidence: 98%
“…Preliminary research reported that lipid disorders (cholesterol and triglycerides) are more frequent in Amerindian-derived populations than in Europeans, justifying our results. 24 However, further studies are required to verify the association across different ethnicities.…”
Section: Discussionmentioning
confidence: 99%